Upholding the World Health Organization: Next steps for the EU - Susan Bergner; Remco van de Pas; Louise G. van Schaik; Maike Voss (Stiftung Wissenschaft und Politik (SWP), 2020)
Before the COVID-19 pandemic, the European Union (EU) was neither a strong promoter of global health nor a strong supporter of the World Health Organization (WHO). The Global Health Council Conclusions from 2010 were never comprehensively implemented and quickly forgotten. With the pandemic greatly affecting EU member states, the EU is increasingly interested in upholding multilateral cooperation in the global health field. Therefore, the EU should aim for an upgrading of the EU's status in WHO, the establishment of a global health unit in the European External Action Service (EEAS), and an overhaul of the formal relationship between the European Commission and WHO.
Keywords: 320